Exposure to a Highly Caloric Palatable Diet During Pregestational and Gestational Periods Affects Hypothalamic and Hippocampal Endocannabinoid Levels at Birth and Induces Adiposity and Anxiety-Like Behaviors in Male Rat Offspring - Ramírez-López, María Teresa; Vázquez, Mariam; Bindila, Laura; Lomazzo, Ermelinda; Hofmann, Clementine; Blanco, Rosario Noemí; Alén, Francisco; Antón, María; Decara, Juan; Ouro, Daniel; Orio, Laura; Suarez, Juan; et al. (Frontiers in Behavioral Neuroscience, 2016)
Exposure to unbalanced diets during pre-gestational and gestational periods may result in long-term alterations in metabolism and behavior. The contribution of the endocannabinoid system to these long-term adaptive responses is unknown. In the present study, we investigated the impact of female rat exposure to a hypercaloric-hypoproteic palatable diet during pre-gestational, gestational and lactational periods on the development of male offspring. In addition, the hypothalamic and hippocampal endocannabinoid contents at birth and the behavioral performance in adulthood were investigated. Exposure to a palatable diet resulted in low weight offspring who exhibited low hypothalamic contents of arachidonic acid and the two major endocannabinoids (anandamide and 2-arachidonoylglycerol) at birth. Palmitoylethanolamide, but not oleoylethanolamide, also decreased. Additionally, pups from palatable diet-fed dams displayed lower levels of anandamide and palmitoylethanolamide in the hippocampus. The low-weight male offspring, born from palatable diet exposed mothers, gained less weight during lactation and, although they recovered weight during the post-weaning period, they developed abdominal adiposity in adulthood. These animals exhibited anxiety-like behavior in the elevated plus-maze and open field test and a low preference for a chocolate diet in a food preference test, indicating that maternal exposure to a hypercaloric diet induces long-term behavioral alterations in male offspring. These results suggest that maternal diet alterations in the function of the endogenous cannabinoid system can mediate the observed phenotype of the offspring, since both hypothalamic and hippocampal endocannabinoids regulate feeding, metabolic adaptions to caloric diets, learning, memory and emotions.